Pyrrolidine Dithiocarbamate Attenuates Cardiocyte Apoptosis and Ameliorates Heart Failure Following Coronary Microembolization in Rats - Shumei Li; Jun Fang; Lianglong Chen (Balkan Medical Journal, 2019)
Background: Nuclear factor-kB is highly activated in cardiovascular disorders. However, few articles have targeted at the role of nuclear factor-kB inhibitor in heart failure. Aims: To evaluate the effects of nuclear factor-kB inhibitor pyrrolidine dithiocarbamate on cardiocyte apoptosis and cardiac function in a rat heart failure model. Study Design: Animal experiment. Methods: A stable and reproducible rat heart failure model (n=64) was prepared by injecting homologous microthrombotic particles into the left ventricle of Sprague–Dawley rats while obstructing the ascending aorta to produce coronary microembolization. Rats with heart failure were randomized into untreated (HFu) and pyrrolidine dithiocarbamate-treated (HFp) groups; the latter received an intraperitoneal injection of pyrrolidine dithiocarbamate (100 mg/kg/day) 1 h prior to surgery as well as on postoperative days 1-7. The sham group comprised 32 Sprague–Dawley rats. Eight rats from each group were sacrificed on days 1, 3, 7, and 14 postoperatively. Masson’s trichrome staining was used to determine the micro-fibrotic area to indicate the severity of myocardial loss. Terminal transferase uridine triphosphate nick end labeling staining was used to detect apoptotic cardiomyocytes. Echocardiography and hemodynamics were performed to evaluate left ventricular function. Results: Rats with heart failure exhibited pathological changes evidenced by patchy myocardial fibrosis, remarkably elevated severity of myocardial loss, and persistently reduced left ventricular function. At the end of the study, compared with the HFu group, myocardial infarct size was reduced by 28% (p=0.001), cardiocyte apoptosis was suppressed (7.17%±1.47% vs 2.83%±0.75%, p<0.001), cardiac function parameters such as left ventricular ejection fraction (80%±4% vs 61%±6%), left ventricular + dP/dt max (4828±289 vs 2918±76 mmHg.s−1), left ventricular - dP/dt max (4398±269 vs 2481±365 mmHg.s−1), and left ventricular systolic pressure (126±13 vs 100±10 mmHg) were significantly increased, and left ventricular end-diastolic pressure was reduced (18±2 vs 13±1 mmHg) (p<0.001, for all) in the HFu group. Conclusion: Our rat model can adequately mimic heart failure via coronary vessel embolization. Moreover, pyrrolidine dithiocarbamate treatment can reduce cardiocyte apoptosis and improve cardiac function, which may be beneficial for patients with heart failure secondary to myocardial infarction.